Kepemimpinan Transformasional Camat dalam Meningkatkan Loyalitas Pegawai di Kantor Kecamatan Selat Penuguan - Dodi Kurnia Adi; Achmad Syarifudin; Hasril Atieq Pohan (Social Science and Contemporary Issues Journal, 2023)
The aim of this research is to analyze the transformational leadership of the sub-district head in increasing employee loyalty at the Penuguan Straits sub-district office and to analyze the supporting and inhibiting factors. The research method used is qualitative. Based on the results of the sub-district head's transformational leadership research in increasing employee loyalty at the Penuguan Straits sub-district office, it has shown good leadership in becoming a leader with a transformational leadership style. Efforts to increase employee loyalty at the Penuguan Straits sub-district office are a must to implement. The sub-district head as a facilitator in the sub-district area has a large role that has been delegated to be able to increase the loyalty of his employees by providing motivation and giving trust to employees in carrying out their respective duties and responsibilities.